Legal Consequences of the Issuance of Government Regulation in Lieu of Law Number 2 of 2022 on the Legal Politics in Indonesia - Abdul Hamid Sobri; Iza Rumesten RS; Suci Flambonita (International Journal of Law, Crime and Justice, 2025)
The issuance of Perppu Number 2 of 2022 has led to various dynamic debates within society. The government's actions have shown attempts to "circumvent" Constitutional Court Decision Number 91/PUU-XVIII/2020 and even eliminate the legislative role in the process of amending laws. Autocratic legalism is a situation where the law is utilized as a tool by the rulers (whether executive, legislative, judicial, or a combination thereof) to legitimize their actions in accumulating and consolidating power under the guise of law. The research findings indicate that the consequences of the issuance of Perppu Number 2 of 2022 include the violation of the legislative drafting grace period, failing to resolve legal uncertainties, and being considered non-aspirational, non-participatory, and non-transparent in its formation.